Comparison of PCR and Viable Count as a Method for Enumeration of Bacteria in an A/J Mouse Aerosol Model of Q Fever - Hartley, M. Gill; Ralph, Esther; Norville, Isobel H.; Prior, Joann L.; Atkins, Timothy P. (Frontiers in Microbiology, 2019)
Historically, disease progression in animal models of Q fever has been carried out using PCR to monitor the presence of Coxiella burnetii DNA in the host. However, the colonization and dissemination of other bacterial infections in animal models are tracked using viable counts, enabling an accurate assessment of viable bacterial load within tissues. Following recent advances in the culture methods, it has become possible to do the same with C. burnetii. Here we compare and contrast the different information gained by using PCR or viable counts to study this disease. Viable bacteria were cleared from organs much faster than previously reported when assessed by bacterial DNA, but weight loss and clinical signs improved while animals were still heavily infected.